2009
DOI: 10.1111/j.1471-0528.2009.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications during pregnancy in women with epilepsy: population‐based cohort study

Abstract: Objective To investigate whether women with epilepsy have an increased risk of complications during pregnancy and to explore the impact of antiepileptic drug (AED) use.Design Population-based cohort study.Setting Data from Medical Birth Registry of Norway based on all births in Norway 1999-2005.Population All births (n = 372 128) delivered in Norway, ensured through linkage with the National Population Registry run by Statistics Norway. All singleton births and the first child in multiple pregnancies were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
110
5
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 34 publications
10
110
5
6
Order By: Relevance
“…For example, women from low SES backgrounds and those who are unmarried (not living with a partner) appear to be more likely to experience maternal health conditions in pregnancy, which may contribute to their increased risk of delivering lower birth weight and/or lower gestational age infants. [54][55][56][57][58][59] The presence of significant effects here by both social disadvantage and health conditions in pregnancy reflect this dual layering of stress sources and the adverse implications for birth outcomes. As noted, cumulative stress models point to dysregulatory cascades across physiological systems, transferring effects of stress to birth outcomes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, women from low SES backgrounds and those who are unmarried (not living with a partner) appear to be more likely to experience maternal health conditions in pregnancy, which may contribute to their increased risk of delivering lower birth weight and/or lower gestational age infants. [54][55][56][57][58][59] The presence of significant effects here by both social disadvantage and health conditions in pregnancy reflect this dual layering of stress sources and the adverse implications for birth outcomes. As noted, cumulative stress models point to dysregulatory cascades across physiological systems, transferring effects of stress to birth outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…52,53 Studies have also shown that pregnancy-related health conditions and maternal health conditions in pregnancy contribute to an increased risk of adverse birth outcomes. [54][55][56][57][58][59] Using data from a prospective cohort study, we examined the pathways linking maternal social disadvantage to birth outcomes. Weathering theory posits that social disadvantage influences health outcomes through physical embodiment mechanisms as well as psychosocial and health behavior pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Women with epilepsy have a low complication rate except of that related to AEDs exposure (Borthen et al, 2009). All of them in childbearing age should be informed about the rates of teratogenicity of AEDs, possibility of increased seizure frequency during pregnancy, and the risks of the pregnancy and labour.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians providing care for pregnant women with epilepsy should be aware of a small but significant increase in the risk of complications during pregnancy, especially in women taking AEDs [4,5,21] [5]. No differences were found between the two groups in terms of perinatal death.…”
Section: Maternity Care During Pregnancymentioning
confidence: 99%